Bridging the Innovation Gap: Strategic Digital Transformation in Indonesia’s Creative Industries - Posma Denny Doly (Journal of Social Research, 2025)
Indonesia's creative industries, particularly the culinary and fashion sectors, are significant contributors to the national economy. However, many micro, small, and medium enterprises (MSMEs) face a persistent innovation gap that limits their competitiveness in the digital era. This study addresses the critical need to understand digital innovation adoption patterns and their impact on business performance within Indonesia's creative economy. The research objectives are threefold: to identify the types of digital innovation being adopted by MSMEs, analyze the key dimensions influencing innovation performance, and propose evidence-based strategies to enhance their competitiveness. Using a quantitative approach, primary data were collected from 384 MSME respondents across various regions in Indonesia through structured questionnaires. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to examine the relationships between variables. The findings confirm that human capital capacity, resource capacity, and strategic environment significantly drive both innovation and operational[A1] performance, which in turn enhance overall business performance. Notably, innovation performance emerged as the strongest predictor of business success, demonstrating its critical role in MSME sustainability. The study provides practical, actionable strategies for policymakers and MSMEs to foster digital transformation, including targeted improvements in digital skills development, enhanced access to funding mechanisms, and sector-specific innovation support programs. These insights contribute to bridging the innovation gap and strengthening Indonesia's positioning in the global creative economy.